2021
DOI: 10.1002/adom.202002267
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Structural Transformation in Sb‐Doped Indium Halides A3InCl6 and A2InCl5∙H2O Yields Reversible Green‐to‐Yellow Emission Switch

Abstract: Lead halide perovskites have demonstrated promising emission tunability achieved by composition engineering, which makes them viable in several potential applications. Determining how to effectively control the crystalline structural transformation and composition in lead‐free halide perovskites is of great importance. Herein, a controllable synthetic method is reported to obtain the 0D metal halide perovskite derivatives (Cs1−xRbx)2InCl5∙H2O and (Cs1−xRbx)3InCl6, through synergistic regulation of the Cs/Rb fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…52 Huang et al observed green emission with PLQY up to 90% in Sb 3+ -doped (Cs 0.29 Rb 0.71 ) 3 InCl 6 , which was attributed to relatively weak electron–phonon coupling and Jahn–Teller distortion. 36 Wei et al achieved high-efficiency green emission by doping Sb 3+ in Cd-based halides. The emission peaks of these halides are all between 500–530 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Huang et al observed green emission with PLQY up to 90% in Sb 3+ -doped (Cs 0.29 Rb 0.71 ) 3 InCl 6 , which was attributed to relatively weak electron–phonon coupling and Jahn–Teller distortion. 36 Wei et al achieved high-efficiency green emission by doping Sb 3+ in Cd-based halides. The emission peaks of these halides are all between 500–530 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The green emission of [Bzmim] 3 SbCl 6 (Bzmim = 1-benzyl-3-methylimidazolium) reported by Huang et al 28 comes from SbCl 6 clusters in the lattice, and Peng et al reported a series of Sb halides, whose red emission comes from SbCl 5 clusters in the compound. 6,29 After doping Sb 3+ in other metal halides, it can achieve blue, 30 green, [31][32][33][34][35][36] yellow, 33,[35][36][37][38][39][40] orange, 31,33 red, 25,39,41,42 near-infrared, 43 and white emission. 38,40 Li et al reported that Sb 3+ doped (BTPP) 2 MnCl 4 (BTPP = benzyltriphenylphosphonium) halides with excitation-dependent dual emission achieve tunable emission colors from green to orange, and (BTPP) 2 MnCl 4 :2.0%Sb crystals exhibit green and orange emission under 254 and 365 nm UV lamps, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The red shift is due to the decreasing of temperature causing the valence band to move to a higher energy level. 44,45 The influence of temperature variation on the PL intensity and shift of emission can be distinctly observed in the pseudocolor mapping of Cu:(PEA) 2 ZnCl 4 and Cu:(PEA) 2 ZnBr 4 (Fig. 3c and f).…”
Section: Resultsmentioning
confidence: 90%
“…43 In addition, in metal halides, the shift of the emission peak caused by temperature change is normally associated with lattice distortion and valence band shift. 43,44 The peaks of Cu:(PEA) 2 ZnX 4 are all red-shifted with decreasing temperature. The red shift is due to the decreasing of temperature causing the valence band to move to a higher energy level.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1d shows the high-resolution XPS spectra of the 3d orbitals of Sb elements in 8.8% Sb:(TDMP)CdCl 4 and (TDMP)CdCl 4 . The peaks at 530 and 539 eV in the figure come from the 3d 5/2 and 3d 3/2 orbitals of Sb 3+ , 36 respectively. This result further indicates that the Sb in these compounds is trivalent Sb 3+ , not other valences.…”
Section: Resultsmentioning
confidence: 99%